Endogenous interleukin‐22 protects against inflammatory bowel disease but not autoimmune cholangitis in dominant negative form of transforming growth factor beta receptor type II mice. (6th June 2016) - Yang, G.‐X.; Sun, Y.; Tsuneyama, K.; Zhang, W.; Leung, P. S. C.; He, X.‐S.; Ansari, A. A.; Bowlus, C.; Ridgway, W. M.; Gershwin, M. E.
Summary: During chronic inflammation, interleukin (IL)‐22 expression is up‐regulated in both CD4 and CD8 T cells, exerting a protective role in infections. However, in autoimmunity, IL‐22 appears to have either a protective or a pathogenic role in a variety of murine models of autoimmunity and, by extrapolation, in humans. It is not clear whether IL‐22 itself mediates inflammation or is a by‐product of inflammation. We have taken advantage of the dominant negative form of transforming growth factor beta receptor type II (dnTGF‐βRII) mice that develop both inflammatory bowel disease and autoimmune cholangitis and studied the role and the biological function of IL‐22 by generating IL‐22 –/– dnTGF‐βRII mice. Our data suggest that the influence of IL‐22 on autoimmunity is determined in part by the local microenvironment. In particular, IL‐22 deficiency exacerbates tissue injury in inflammatory bowel disease, but has no influence on either the hepatocytes or cholangiocytes in the same model. These data take on particular significance in the previously defined effects of IL‐17A, IL‐12p40 and IL‐23p19 deficiency and emphasize that, in colitis, there is a dominant role of IL‐23/T helper type 17 (Th17) signalling. Furthermore, the levels of IL‐22 are IL‐23‐dependent. The use of cytokine therapy in patients with autoimmune disease has significant potential, but must take into account the overlapping and often promiscuous effects that can theoretically exacerbate inflammation.